2018
DOI: 10.1101/gr.236885.118
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum: Evolutionary expansion of DNA hypomethylation in the mammalian germline genome

Abstract: Corrigendum: Evolutionary expansion of DNA hypomethylation in the mammalian germline genome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…This shows that many MDH loci are specifically hypomethylated in mice but not in dogs. This is consistent with previous observations showing that murid genomes have accumulated many new HMRs compared to other mammals (Qu et al, 2018). To test whether these shifts in methylation levels are associated with changes in recombination activity, we computed the LD-based recombination rate in dogs as a function of the distance to the closest MDH locus, separating those whose midpoints overlap a HMR in dogs (7,186), and those that do not (7,283)(Fig.…”
Section: Conservation Of Recombination Hotspots Between Prdm9-deficie...supporting
confidence: 85%
See 4 more Smart Citations
“…This shows that many MDH loci are specifically hypomethylated in mice but not in dogs. This is consistent with previous observations showing that murid genomes have accumulated many new HMRs compared to other mammals (Qu et al, 2018). To test whether these shifts in methylation levels are associated with changes in recombination activity, we computed the LD-based recombination rate in dogs as a function of the distance to the closest MDH locus, separating those whose midpoints overlap a HMR in dogs (7,186), and those that do not (7,283)(Fig.…”
Section: Conservation Of Recombination Hotspots Between Prdm9-deficie...supporting
confidence: 85%
“…Indeed, indirect evidences suggested that recombination hotspots in dogs are associated to germline hypomethylated regions (HMRs) (Berglund et al, 2015). Using HMRs identified by bi-sulfite sequencing in dog sperm (Qu et al, 2018), we observed that 74% of dog hotspots are located inside HMRs, which represent only 3.7% of the dog genome. In mice, the overlap is even stronger: using HMRs identified in mouse sperm (Hammoud et al, 2014), we observed that out of the 30,929 hotspots found in the Prdm9 / mutant, 93% are located within HMRs, which cover only 4.6% of the mouse genome (see methods for details).…”
Section: Conservation Of Recombination Hotspots Between Prdm9-deficie...mentioning
confidence: 88%
See 3 more Smart Citations